Korekcija između NLRP6 upalama i nivoa upalnih citokina IL-1 β i IL-18 u serumu bolesnika s Menierinom bolešću - Li, Mengxiao; Zhou, Ying; Liu, Zhibiao; Jin, Xin (Journal of Medical Biochemistry, 2025)
Background: Meniere’s disease (MD) is a prevalent condition in the field of otolaryngology, with its incidence rate showing an annual increase. Consequently, understanding the underlying mechanisms of MD is of significant importance. Objective: The aim is to investigate the relationship between serum levels of interleukin-1β (IL-1β) and interleukin-18 (IL-18), as well as the activation status of NLRP6 inflammasomes, in patients with Meniere’s disease, and to evaluate their correlation with the severity of the disease, so as to improve the treatment strategy of Meniere’s disease. Method: From March 2021 to December 2023, 75 MD patients were selected from the Affiliated Huaian No.1 People’s Hospital of Nanjing Medical University for research, and a control group consisting of 75 age-matched healthy individuals was established. Each participant contributed a 5 ml sample of peripheral venous blood, which was subsequently archived at -80°C for subsequent analyses. The expression levels of NLRP6 messenger RNA in the blood samples were quantified using real-time fluorescence quantitative PCR methodology. Concentrations of interleukin-1β (IL-1β) and interleukin-18 (IL-18) were measured via enzyme-linked immunosorbent assay (ELISA). Through a comparative examination of NLRP6, IL-1β, and IL-18 levels between MD patients and the healthy controls, the study delved into the potential association between NLRP6 expression and the circulating levels of these two cytokines. In addition, special attention is paid to the differences between unilateral and bilateral MD patients in the above three indexes, in order to evaluate their effectiveness as potential biomarkers for predicting the severity of hearing loss in MD patients. Results: In individuals suffering from MD, a notable elevation was observed in the peripheral blood expression levels of NLRP6, IL-1β, and IL-18. A correlation assessment disclosed a positive association between the blood NLRP6 content and both IL-1β and IL-18 concentrations among these patients. Notably, no substantial disparity emerged in the expression profiles of these three biomarkers when comparing unilateral versus bilateral MD cases. Furthermore, patients at advanced stages (III+IV) exhibited significantly heightened levels of NLRP6, IL-1β, and IL-18 compared to their counterparts in earlier stages (I+II). Receiver operating characteristic (ROC) curve analyses demonstrated that the area under the curve (AUC) for NLRP6, IL-1β, and IL-18 stood at 0.8731, 0.8089, and 0.7838, respectively, suggesting their potential as proficient diagnostic markers capable of differentiating MD patients from healthy controls. Conclusions: NLRP6, IL-1 β, and IL-18 are highly expressed in the peripheral blood of MD patients. NLRP6, IL-1 β, and IL-18 can serve as early diagnostic indicators for MD disease